"Dry mouth" and "Flammer" syndromes-neglected risks in adolescents and new concepts by predictive, preventive and personalised approach - Kunin, Analtoly; Polivka, Jiri; Moiseeva, Natalia; Golubnitschaja, Olga (The EPMA journal, 2018)
BACKGROUND: "Dry mouth" syndrome (chronic hyposalivation) can be caused by a number of pathophysiological conditions such as acute and chronic stress exposure, abnormal body weight (both too high and too low ones), eating disorders (such as anorexia nervosa), metabolic syndrome(s), Sjögren's and Sicca syndromes, drugs and head/neck radiotherapy application. In turn, the chronic hyposalivation as a suboptimal health condition significantly reduces quality of life, may indicate a systemic dehydration, provokes and contributes to a number of pathologies such as a strongly compromised protection of the oral cavity, chronic infections and inflammatory processes, periodontitis, voice and digestive disorders. Consequently, "dry mouth" syndrome might be extremely useful as an indicator for an in-depth diagnostics of both-co-existing and snowballing health-threating conditions. However, predictive diagnostics, targeted prevention and personalisation of treatments are evidently underdeveloped for individuals at high risk suffering from the "dry mouth" syndrome. WORKING HYPOTHESIS AND METHODOLOGY: In the current study, we have hypothesised that individuals demonstrating "Flammer syndrome" (FS) phenotype may suffer from the "dry mouth" syndrome more frequently, due to disturbed microcirculation, psychological factors (obsessional personality/perfectionism), and diminished feeling of thirst with consequently insufficient daily liquid intake potentially resulting in the systemic dehydration with individually pronounced level of severity. If confirmed, FS phenotyping linked to the chronic hyposalivation might be predictive for individuals at risk identified by innovative screening programmes. To verify the working hypothesis, healthy individuals (negative control group) versus individuals with evident hyposalivation as well as patients diagnosed with periodontitis (positive control group) observed and treated at the dental clinic were investigated. The degree to which an individual is affected by hyposalivation was determined by the Bother xerostomia Index utilising a questionnaire of 10 issue-specific items and monitoring of a typically matt roof of the mouth in dental practice. An extent to which individuals included in the study are the carriers of the FS phenotype was estimated by the specialised 15-item questionnaire. RESULTS AND CONCLUSIONS: For both-the target group (hyposalivation) and positive control group (periodontitis)-FS phenotype was demonstrated to be more specific compared to the disease-free (negative control) group. Moreover, self-reports provided by interviewed adolescents of the target group frequently recorded remarkable discomfort related to "dry mouth" syndrome, acute and chronic otorhinolaryngological infections and even delayed wound healing. Further, interviewed adolescents do worry about the symptoms which might be indicative for potential diseases; they are also amazed that too little attention is currently paid to the issue by caregivers. In conclusion, FS questionnaire linked to the "dry mouth" syndrome is strongly recommended for application in primary healthcare. Consequently, targeted preventive measures can be triggered early in life. For example, traditional, complementary and alternative medicine demonstrates positive therapeutic effects in individuals suffering from xerostomia. For in-depth diagnostics, epi/genetic regulations involved into pathophysiologic mechanisms of hyposalivation in FS-affected individuals should be thoroughly investigated at molecular level. Identified biomarker panels might be of great clinical utility for predictive diagnostics and patient stratification that, further, would sufficiently improve personalised care to the patient.
Keywords: Impaired wound healing; Voice disorder; Predictive preventive personalised medicine; Sicca syndrome; Flammer syndrome; Phenotype; Patient stratification; Periodontitis; Xerostomia; Dehydration; Digestive disorder; Hyposalivation